An Empirical Study on the Influence of the Mobile Information System on Sports and Fitness on the Choice of Tourist Destinations - Yan Weng (Hindawi Limited, 2021)
Based on the popularity of mobile information and the important role of mobile information in marketing, the use of mobile information to publish travel information and travel advertisements has become a new choice for operators, which can also attract sports and fitness people. This article studies the influence of official microblog of tourist destination on tourists’ choice of tourist destination. In this study, five factors, such as the usefulness of official microblog, are taken as independent variables, tourist destination selection as dependent variables, and the mediating role of use attitude is taken into account. A research model is established to explore the impact of these variables on tourist destination selection. The results show that usefulness, ease of use, interactivity, and entertainment have direct effects on tourists’ willingness to choose tourist destinations; ease of use and interactivity can indirectly affect tourists’ choice of tourist destinations using attitudes; perceived trust needs to have a positive effect on tourists’ willingness to choose tourist destinations using attitudes.